A Novel Prophage-like Insertion Element within yabG Triggers Early Entry into Sporulation in Clostridium botulinum - François P. Douillard; Inês Martins Portinha; Yağmur Derman; Cédric Woudstra; Tommi Mäklin; Martin B. Dorner; Hannu Korkeala; Adriano O. Henriques; Miia Lindström (Viruses, 2023)
Sporulation is a finely regulated morphogenetic program important in the ecology and epidemiology of Clostridium botulinum. Exogenous elements disrupting sporulation-associated genes contribute to sporulation regulation and introduce diversity in the generally conserved sporulation programs of endospore formers. We identified a novel prophage-like DNA segment, termed the yin element, inserted within yabG, encoding a sporulation-specific cysteine protease, in an environmental isolate of C. botulinum. Bioinformatic analysis revealed that the genetic structure of the yin element resembles previously reported mobile intervening elements associated with sporulation genes. Within a pure C. botulinum culture, we observed two subpopulations of cells with the yin element either integrated into the yabG locus or excised as a circular DNA molecule. The dynamics between the two observed conformations of the yin element was growth-phase dependent and likely mediated by recombination events. The yin element was not required for sporulation by C. botulinum but triggered an earlier entry into sporulation than in a related isolate lacking this element. So far, the yin element has not been found in any other C. botulinum strains or other endospore-forming species. It remains to be demonstrated what kind of competitive edge it provides for C. botulinum survival and persistence.